2018
DOI: 10.1111/1758-2229.12624
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and invasion attributes of Burkholderia pseudomallei are dependent on airway surface liquid and glucose concentrations in lung epithelial cells

Abstract: Physiological constituents in airway surface liquids (ASL) appear to impact the adherence and invasion potentials of Burkholderia pseudomallei contributing to recrudescent melioidosis. Here, we investigated the factors present in ASL that is likely to influence bacterial adhesion and invasion leading to improved understanding of bacterial pathogenesis. Six B. pseudomallei clinical isolates from different origins were used to investigate the ability of the bacteria to adhere and invade A549 human lung epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…B. pseudomallei produce bongkrekic acid (BA) in the host cell during the infection stage, and BA is toxic to the mitochondrial of host cells by inhibiting adenine nucleotide translocase 35 . Which resulted in a significant decrease in ATP production in Bp group, but glucose was taken up to help the adhesion and invasion of B. pseudomallei HNBP001 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. pseudomallei produce bongkrekic acid (BA) in the host cell during the infection stage, and BA is toxic to the mitochondrial of host cells by inhibiting adenine nucleotide translocase 35 . Which resulted in a significant decrease in ATP production in Bp group, but glucose was taken up to help the adhesion and invasion of B. pseudomallei HNBP001 36 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that diabetes results in blunted B. pseudomallei -specific cellular responses during acute infection 38 and possibly due to glucose affecting the thioester bond of neutrophils complement C3 and thereby preventing binding to the bacterial surface 39 . Another study showed that glucose significantly increased adherence and invasion of B. pseudomallei to A549 cells 36 , but the mechanism is still unclear. Here, we present a new potential mechanism: abnormal glucose metabolism leads to O-GlcNAc modification abnormally; O-GlcNAcylation may affect the ability of host cells to respond to B. pseudomallei through regulating the function and structure of host cell proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study revealed that acidic microenvironment could significantly enhance the activation of IRF3 followed by P. aeruginosa infection or OMVs stimulations, which in turn led to an increase in IFN-β production and promoted the colonization of P. aeruginosa , thus leading to the deterioration of infection. Mariappan et al reported that the ability to adhere lung epithelial cells by B.pseudomallei was modulated by pH and glucose concentrations, without mentioning the underlying mechanism [ 44 ]. Our novel findings indicated that IFN-β blocking or inhibition could reduce the increased bacterial colonization and the aggravated host damage after P. aeruginosa infection that exacerbated by acidic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50][51] Enhanced adhesion and invasion potential of B. pseudomallei has been linked to glucose concentrations, which may also explain the increased susceptibility of patients with diabetes developing melioidosis. 52 Around 9 to 50% of patients with melioidosis-depending on cohort studied-had underlying renal disease. 53,54 This was statistically different from other causes of sepsis.…”
Section: Host Immune Response and Risk Factorsmentioning
confidence: 99%